Optimizing Education for a Healthy Nation: Array - Bashtovenko, Oksana (Journal of Danubian Studies and Research, 2020)
New methodological approaches to optimizing education are based on solving the complex problem of fostering a health culture. This will make it possible to improve health not only for schoolchildren, but also for the future, people of different ages. The main share of responsibility for maintaining the health of schoolchildren lies with a physical education specialist. Increased attention and great responsibility rests on high-quality training of specialists in this field. The creation of high-tech, interactive organizational and pedagogical conditions will provide an opportunity for high-quality professional self-determination of future specialists. Optimal opportunities for building health skills will be realized.